Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Savi (Somatis, Auditori, Visual,Intelektual) pada Mata Pelajaran Fiqih Kelas VIII di MTs Al-Amanah Al-Gontory Tangerang Selatan - Heriyanto, Toto; Afif, Nur; Zakia, Zulva Ummi (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to improve student learning outcomes through the SAVI (Somatic, Auditory, Visual, Intellectual) learning model in class VIII fiqh subjects at Mts Al-Amanah AlGontory, South Tangerang. This study uses a qualitative research method Classroom Action Research (PTK) where the teacher is the researcher and observer. This research was conducted in the odd semester of the 2022/2023 school year, namely in September. The subjects of this study were students of class VIII Mts Al-Amanah Al-Gontory consisting of 35 people. Data collection techniques in this study were observation, interviews, written tests and documentation. Data were analyzed descriptively and presented in tabular form. The results showed an increase in student learning outcomes after using the SAVI learning model, namely in the first cycle by 60% and in the second cycle by 89%. This means that there is an increase of 29% from cycle I to cycle II. Thus the use of the SAVI learning model in fiqh subjects can improve student learning outcomes in class VIII Mts Al-Amanah Al-Gontory. Keywords: Learning Outcomes, SAVI learning model, Fiqh